Community-Based Nursery Initiation to Improve Community’s Income Surrounding KHDTK DIKLATHUT UGM, Ngawi District, East Java - Atmanto, Winastuti Dwi; Sawitri, Sawitri; Ratnaningrum, Yeni Widyana Nurchahyani (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
Indonesia’s commitment to addressing climate change was declared at the 27th Conference of the Parties (COP) in 2021, with its Intended Nationally Determined Contribution (NDC) pledging to reduce greenhouse gas (GHG) emissions by 31.89% (unconditional) and 43.2% (conditional) by 2030. The forestry sector played a vital role by accelerating forest cover through restoration and rehabilitation programs. KHDTK DIKLATHUT UGM (KDU) consistently organized such programs by planting various species. To fulfill seedling needs, local communities were involved through community-based nursery initiatives. The establishment of the community-based nursery program aimed to: (1) encourage community participation around the forest to support the success of the KHDTK DIKLATHUT UGM forest restoration and rehabilitation program, (2) develop competent local community cadres skilled in producing high-quality seedlings for plantation, and (3) provide additional job opportunities and increase income for the local community. Three targeted villages were located in Ngawi: Pitu, Kalang, and Nglebak. The methods used in this program included: (1) focus group discussions (FGDs), (2) field observation and surveys, (3) education and training, and (4) monitoring and evaluation. The results showed that 12 local communities had established community-based nurseries with various species being propagated. The program also demonstrated good financial feasibility, generating a profit of IDR69,272,273 or approximately IDR289 per seedling. However, seedling handling and health maintenance remained challenging. Therefore, further education and training could be initiated to improve the local community’s knowledge and skills.